2016
DOI: 10.1108/ara-11-2013-0072
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance and auditor quality – Malaysian evidence

Abstract: Purpose The purpose of this paper is to conduct an investigation into the relationship between a firm’s corporate governance mechanisms (audit committee composition and operation, block shareholder, CEO duality, financial state, ownership dominance, political connection, share price, and family control) and auditor quality selection in Malaysia, for periods before and after the introduction of Malaysian Code of Corporate Governance in 2007 (MCCG 2007). De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 143 publications
5
55
1
3
Order By: Relevance
“…Husnin, Nawawi, and Salin () found that in general corporate governance practices influence auditor selection through restructuring of corporate governance tools, such as audit committee and internal audit functions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Husnin, Nawawi, and Salin () found that in general corporate governance practices influence auditor selection through restructuring of corporate governance tools, such as audit committee and internal audit functions.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In addition, the study provides supporting evidence for the complementary association between a company's governance and audit fees. Husnin, Nawawi, and Salin (2016) found that in general corporate governance practices influence auditor selection through restructuring of corporate governance tools, such as audit committee and internal audit functions.…”
Section: Corporate Governance and Audit Qualitymentioning
confidence: 99%
“…Transparency must be visible, which should take the form of consistent records and reports on income. Husnin et al, (2016) demonstrated that expropriation, potentialconflicts of interests and unfair of minority shareholders can result because of poor CG. It only serves the individuals involved but-do notaffect the value of other stakeholders.…”
Section: Drmohamed Samy El-deeb Lamis Mustafa Elsharkawymentioning
confidence: 99%
“…Both monitoring and advising were the most powerful activities; where advising means assisting the top management team in creating and keeping strategies for achieving the goals of the company (Ali, 2018). Husnin et al, (2016) agreed that the implementation of CG is a crucial factor that helps companies to secure and attain their sustainability and competitiveness within the business environment. The practices of different mechanisms of CG did not only serve the business internal process, but also create external support to stockholders, creditors, and other stakeholders.…”
mentioning
confidence: 99%
“…Researchers (e.g., Fan and Wong, 2005;Eshleman and Guo, 2014;Asthana et al 2015;Knechel, 2016) have typically viewed 'Big' audit firms to provide higher quality audit than 'non-Big' firms as a result of their competitive advantages in terms of scale of operations, technical competencies, and market reputation. Accordingly, several audit studies (e.g., Firth and Smith, 1992;Beasley and Petroni, 2001;Lin and Liu, 2009;Hsu et al 2015;Husnin et al 2016;Lai et al 2017) were carried out to investigate factors related to audit client's choice to hire "Big 4" vs. "non-Big 4" external audit firm. Although audit research has investigated auditor choice for quite some time, a relatively recent stream of this research has focused on the effect of CG factors on this choice (Hay et al 2006).…”
Section: Introductionmentioning
confidence: 99%